Polyphenols and antioxidant activity of aqueous extract of Musa Acuminata Cavendish Subgroup (BANANA) - Marín-Velázquez, María (2020)
The objective of this work was to determine the total polyphenol content and evaluate the antioxidant activity by the 2,2-diphenyl-1-picrilhydrazil (DPPH) method in a lyophilized aqueous extract of the Musa canvedish “Banana” peel. The treatment of 300 g of the sample was carried out by running through water at 90 ° C for 20 seconds, immediately 500 ml of a mixture of water and 96% ethanol in a ratio (1:1) were added, immediately crushing was performed, centrifugation and filtration of the diluted sample. The ethanol fraction was separated with the use of a rotary evaporator for subsequent lyophilization of the liquid fraction. The quantification of polyphenols was performed using the Folin Ciocalteu method and the antioxidant activity was used by the DPPH radical method. All tests are performed in triplicate, calculating the standard deviation and the multiple comparisons test for antioxidant activity. The total polyphenol content was 5,7811 µg equivalent of gallic acid / 1g of Musa acuminata Cavendish Subgroup extract. The percentage of inhibition by the DPPH radical method with a percentage of 33,333; fifty; 66,667 and 100 µg / mL were 20,959; 31,428; 41,030 and 60,290%, respectively. The mean inhibitory concentration was (IC 50) of 81.95 µg / mL. It is concluded that the lyophilized extract of Musa canvedish “Banana” has polyphenols and moderate antioxidant activity, being an interesting sample for future research.